The Place of Roman Law Sources in the Development of Pre-Classical Canon Law (ius antiquum) - Lukošius, Tadas (Teisė, 2022)
The paper examines the place of Roman law sources in the development of pre-classical or old canon law (ius antiquum). By looking at the evolution of ius antiquum from the perspective of changing Church-state relations, the author seeks to identify as to whether – and if yes, to what extent – sources of ius antiquum relied on the sources of Roman law.
Keywords: canon law; ius antiquum; roman law; Justinian’s codification